DIGITAL FLIPBOOK MEDIA ON PANCASILA VALUES MATERIAL TO IMPROVE READING LITERACY OF GRADE II ELEMENTARY SCHOOL STUDENTS - Ayu Dwipayani, Ni Made; Suastika, I Nengah; Parmiti, Desak Putu (Pena Cendekia Insani, 2026)
This study aimed to develop a digital flipbook media containing Pancasila values for second-grade elementary school students that is valid, practical, and effective. The study employed a development research method by adapting the Borg and Gall development model, resulting in a digital flipbook entitled “Aku Anak Pancasila; Ayo, Jadi Hebat Dengan Lima Sila!”. Media validity was assessed by experts in media, content, and language. The practicality of the media was evaluated by six elementary school teachers, three students in individual trials, and ten students in small-group trials. The effectiveness test used a one-group pretest–posttest design involving 20 second-grade students. Data were analyzed using qualitative and quantitative techniques with a Likert scale. The results showed that the overall validity score reached 96.72%, categorized as very valid. The practicality scores were 95.5% from teachers and 91.1% from students, both categorized as very practical. The effectiveness test using a paired-sample t-test yielded a significance value of 0.002, indicating that the media is effective. In conclusion, the digital flipbook media is feasible and effective for improving students’ reading literacy.